Determinants of prolonged length of hospital stay after cardiac surgery: impact of rheumatic heart disease - Pato,Mariângela F (2015)
BACKGROUND: Rheumatic heart disease remains a major health problem in developing countries. Several factors contribute to valve-related morbidity after cardiac surgery, but the role of rheumatic etiology of valve disease is not well defined. This study was designed to determine the additional value of rheumatic valve disease in predicting morbidity after cardiac surgery in the current era of heart valve disease treatment. METHOD: This study prospectively included 164 patients for cardiac surgery from June 2010 to June 2011. The outcome was prolonged length of stay, defined as a length of stay greater than or equal to the 75th percentile for length of stay for each operation, including the day of discharge. RESULTS: Rheumatic heart disease was present in 32 patients (20%) and all rheumatic patients underwent valve replacement. Rheumatic heart disease patients were younger with less comorbidities compared to non-rheumatic patients, with most (63%) having had previous surgery. Forty-one patients were classified as having a prolonged hospital length of stay; 11 (34%) patients with rheumatic and 30 (23%) non-rheumatic fever. Rheumatic heart disease was not associated with prolonged hospital stay in the univariate analysis; however, after adjustment for other factors including infectious endocarditis, surgery duration, mechanical ventilation time, EuroSCORE, and postoperative pneumonia, it was found to be a predictor of prolonged hospitalization. CONCLUSION: This study demonstrates that rheumatic heart disease was an important factor associated with prolonged hospital, after adjustment for well-known risk factors of morbidity after cardiac surgery. Rheumatic fever is still prevalent among the patients who underwent to cardiac surgery in the current age, contributing to increase the postoperative morbidity.